Antiulcerative and antioxidant action of hydroalcoholic extract of Anacardium occidentale L. leaves in an induced experimental colitis model - Victor Pedro; Maria do Socorro Medeiros Amarante; Everlândja Gomes de Almeida; Manoel André de Souza Neto; Silvana Maria Zucolotto; Matheus Augusto de Bittencourt Pasquali; Sérgio Adriane Bezerra de Moura; Fabiane Ferreira Martins; Christina da Silva Camillo (Acta Cirúrgica Brasileira, 2025)
ABSTRACT Purpose: To examine the antiulcerative and antioxidant action of the Anacardium occidentale hydroalcoholic leaf extract (HEA) on experimentally induced colitis in rats via acetic acid (AA). Methods: Male rats were distributed into six groups (n = 10 per group): C (control), CC (colitis control), SZC (sulfasalazine 500 mg/kg), and three doses of HEA (HEA50 = 50 mg/kg, HEA100 = 100 mg/kg, HEA200 = 200 mg/kg). Results: The treatment with HEA100 for seven days decreased diarrhea, increased food intake, attenuated weight loss, and recovered the macroscopic and histological parameters of the colon, mitigating the severity of colitis and restoring the intestinal morphophysiology of animals with induced colitis. Additionally, HEA50 and HEA100 treatment increased the activity of superoxide dismutase, catalase, and thiol, and reduced the levels of thiobarbituric acid reactive substances and carbonyl, contributing to the re-establishment of antioxidant homeostasis. Conclusion: This study provided preclinical evidence of the potential of A. occidentale leaf extract, particularly at the concentration of 100 mg/kg, as an antiulcer agent for attenuating colitis in rats, likely due to the positive modulation of the antioxidant system.